Evaluating the physiological and biochemical responses of different mangrove species to upwelling - Li, Xiaomei; Wang, Yutu; Zhang, Yuhang; Xiang, Jingchang; Yang, Zhihao; Gu, Fangfang; Wu, Meilin (Frontiers in Marine Science, 2022)
Mangroves are unique forest communities with an abundance of species, high productivity and high ecological, social and economic value. Evaluation of the stress resistance of mangrove plants has mainly focused on the effects of high salinity, heavy metals and flooding, with fewer studies evaluating resistance to upwelling stress. Mangrove species of Avicennia marina, Aegiceras corniculatum and Kandelia obovata were submitted to three temperature upwelling (5, 10 and 15°C) and several physiological and biochemical parameters were measured at six time points (0, 6, 12, 24, 72 and 168 h). The data demonstrated: a certain amount of damage occurred to mangrove plants in the face of prolonged upwelling; different mangrove plants have different response strategies to upwelling; mangrove plants are not sensitive to different upwelling temperatures; the resistance of mangrove plants to upwelling stress was in the following order: A. marina< K. obovata< A. corniculatum. Markers of damage such as relative electrical conductivity (REC), malondialdehyde (MDA) and reactive oxygen species (ROS) among all mangrove species were significantly higher with prolonged upwelling stress. The contents of photosynthetic pigments in all three mangrove species also increased. Superoxide dismutase activity (SOD) was maintained at a high level in both control and treatment groupss. By contrary, the change of peroxidase activity (POD) of A. marina and K. obovata was larger than that of A. corniculatum. Catalase activity (CAT) in A. marina and K. obovata significantly increased under upwelling at both 5 and 10°C while there was no obvious variation of CAT in A. corniculatum. Soluble protein and Soluble sugar contents showed no clear variation but stayed at fairly high levels. However, proline content in A. corniculatum significantly increased under long-term upwelling stress while this was not the case in the other two species. High correlation could be observed between A. marina and MDA, O2- and POD in PCA while A. corniculatum showed association with proline and soluble sugar. In conclusion, the ability of A. corniculatum to tolerate upwelling stress might be due mainly to increases in the activities of SOD and the inducing of proline biosynthesis, while, A marina and K. obovata tolerated upwelling stress by adjusting activity levels of SOD, POD and CAT. Segregation in both principal component analysis (PCA) and hierarchical cluster analysis (HCA) further indicated different tolerances and resistances to upwelling between the three species. Our study provides new insights into the stress response of mangroves to upwelling.